PACAP and PAC1 Receptor Expression in Human Insulinomas - Sandor Ferencz; Denes Toth; Balint Kaszas; Sebastian Bardosi; Viktoria Vicena; Oszkar Karadi; Dora Reglodi; Dezso Kelemen (International Journal of Peptide Research and Therapeutics, 2021)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide with widespread occurrence and diverse functions. PACAP binds to specific PAC1 and non-specific VPAC1/2 receptors. PACAP is considered as a growth factor, as it plays important roles during development and participates in reparative processes. Highest concentrations are found in the nervous system and endocrine glands, where several functions are known, including actions in tissue growth, differentiation and tumour development. Therefore, we have investigated expression of PACAP and its receptors in different tumours, including those of endocrine glands. We showed earlier that PACAP and PAC1 receptor staining intensity decreased in pancreatic ductal adenocarcinoma. In the present study we aimed to investigate alterations of PACAP and PAC1 receptor in human insulinoma and compared the immunostaining pattern with samples from chronic pancreatitis patients. We collected perioperative and histological data of patients who underwent operation because of insulinoma or chronic pancreatitis over a five-year-long period. Histology showed chronic pancreatitis with severe scar formation in pancreatitis patients, while tumour samples evidenced Grade 1 or 2 insulinoma. PACAP and PAC1 receptor expression was studied using immunohistochemistry. Staining intensity was very strong in the Langerhans islets of normal tissue and discernible staining was also observed in the exocrine pancreas. Immunostaining intensity for both PACAP and PAC1 receptor was markedly weaker in insulinoma samples, and disappeared from chronic pancreatitis samples except for intact islets. These findings show that PAC1 receptor/PACAP signalling is altered in insulinoma and this suggests a possible involvement of this system in tumour growth or differentiation.

Diagnostic muscle biopsies in the era of genetics: the added value of myopathology in a selection of limb-girdle muscular dystrophy patients - Boel De Paepe; Elise Velghe; Linnea Salminen; Balint Toth; Pieter Olivier; Jan L. De Bleecker (Acta Neurologica Belgica, 2021)

Traumatic brain injury-induced cerebral microbleeds in the elderly - Luca Toth; Andras Czigler; Peter Horvath; Balint Kornyei; Nikolett Szarka; Attila Schwarcz; Zoltan Ungvari; Andras Buki; Peter Toth (GeroScience, 2021)
Traumatic brain injury (TBI) was shown to lead to the development of cerebral microbleeds (CMBs), which are associated with long term cognitive decline and gait disturbances in patients. The elderly is one of the most vulnerable parts of the population to suffer TBI. Importantly, ageing is known to exacerbate microvascular fragility and to promote the formation of CMBs. In this overview, the effect of ageing is discussed on the development and characteristics of TBI-related CMBs, with special emphasis on CMBs associated with mild TBI. Four cases of TBI-related CMBs are described to illustrate the concept that ageing exacerbates the deleterious microvascular effects of TBI and that similar brain trauma may induce more CMBs in old patients than in young ones. Recommendations are made for future prospective studies to establish the mechanistic effects of ageing on the formation of CMBs after TBI, and to determine long-term consequences of CMBs on clinically relevant outcome measures including cognitive performance, gait and balance function.